Metallic conductivity in complex lanthanum nickelates - Дзязько, О.; Неділько, С.; Куліченко, В. (Київський національний університет імені Тараса Шевченка, 2017)
Complex Lanthanum nickelates were produced by the co-precipitation method with further heat-treating of the obtained batch. Researched the influence of Lanthanum nickelates composition on resistive qualities of the obtained samples. Studied the phase and chemical composition of the obtained complex oxide compounds and oxygen nonstoichiometry. It is demonstrated that Ni-based and La-based complex oxide systems related to Ruddlesden-Popper (RP) phase of total composition Lan+1NinO3n+1 (1≤n≤3) show anomalously high conductivity. For the system La2-xNiO4-d in the range 0,6≤x≤1 revealed metal character of conductivity-temperature dependence. For substituted RP phases  La3-xMexNi2O7-δ and La4-xMexNi3O10-δ (Me=Ca, Sr, Ba) high conductivity belongs to the compounds in which ionic radius of substituent exceed ionic radius of Lanthanum in case of single-phase compound. When the number of substituents is increased for the listed above systems, transition takes place from metal conductivity to semi-conductivity and dielectric conductivity. Therefore, electric conductivity of oxide compounds with RP phase structure essentially depends on density of conduction electrons in unit cell. Change of conduction dependence may be also related to structural imperfection of the formed RP phases, and replacement of more conductive layers Lanthanum-Oxygen with less conductive layers alkaline-earth metals-oxygen. Increase of containing of trivalent Nickel leads to the increase of overlapping degree of dx2-y2 and рO2-orbital’s of ions in equatorial planes, and, correspondingly, decrease of energy barrier between conduction band and valence band. Because of that, the temperature of transition semiconductor-metal significantly decreases and electric conductance in chains -O2--Ni3+-O2--Ni2+-O2-- increases. When content of trivalent Nickel in complex oxide is over 50%, Lanthanum nickelates demonstrate metal conduction type.

Синтезовано складні нікелати лантану за методом сумісного осадження компонентів з наступною термічною обробкою отриманої шихти. Досліджено вплив складу нікелатів лантану на резистивні властивості одержаних зразків. Вивчено фазовий та хімічний склад одержаних складнооксидних сполук, а також кисневу нестехіометрію. Показано, що складні оксидні  системи на  основі нікелю  та  лантану, що відносяться  до  фаз Руддлесдена-Поппера (ФРП)  загального  складу Lan+1NinO3n+1 (1≤n≤3) проявляють аномально високу провідність. Для системи La2-xNiO4-δ в інтервалі 0,6≤x≤1 виявлено металічний  характер залежності  електричної  провідності  від  температури.  Для заміщених  ФРП  складу La3-xMexNi2O7-δ  і La4-xMexNi3O10-δ (Me=Ca, Sr, Ba) високу провідність мають сполуки, в яких іонний радіус замісника перевищує іонний радіус лантану за умови однофазності сполуки. При збільшенні кількості замісників для вищевказаних систем відбувається перехід від металічної провідності до напівпровідникової та діелектричної. При вмісті тривалентного нікелю в складному оксиді більше 50 %, у нікелатів лантану реалізується металічний тип провідності.
Металічна провідність в складних нікелатах лантану
Keywords: metal conductivity; Ruddlesden-Popper (RP) phases; oxygen nonstoichiometry; resistance properties; Lanthanum nickelates; Сonductivity; металічна провідність; фази Руддлесдена-Поппера (ФРП); киснева нестехіометрія; резистивні вла-стивості; Нікелати лантану; Провідність